How does air pollution affect travel behavior? A big data field study. (October 2021) - Xu, Yuquan; Liu, Yuewen; Chang, Xiangyu; Huang, Wei
Highlights: This paper reports the first attempt to study the general impact of air pollution on a large population's travel behavior via "big field data": 4.6 billion mobile positioning records of 813, 360 people during 61 winter days. Comparing to the mixed findings in the literature, we find that air pollution does have a significantly negative impact on travel behavior. People reduce their travel distance slightly but reduce their travel area greatly on air polluted days. In detail, people reduce the average RG by 0.76%, but reduce the average NP by 6.57% as AQI increases 100 points. People in different demographic groups react to air pollution differently. Younger people (50 and under) reduce more NP, while older people (above 50) reduce more RG on heavily air polluted days. Abstract: Exposure to ambient air pollution causes 4.2 million deaths worldwide every year; thus, people may avoid traveling on polluted days. However, the extant studies have mixed findings of the travel behavior on polluted days, caused by the shortcomings of survey data and specific activity data. In order to fulfill this research gap, this study evaluates the relationship between air pollution and travel behavior based on approximately 4.6 billion mobile positioning records in Xi'an, China. Moreover, this study also investigates how different demographic groups travel differently on polluted days. The results indicate that air pollution has a significantly negative correlation with travel behavior. Specifically, (1) people reduce travel distance slightly but reduce travel area greatly; and (2) younger people (50 and under) reduce more travel area while older people (over 50) reduce more travel distance on polluted days.